Filtering populist claims to fight populism : the Italian case in a comparative perspective - Martinico, Giuseppe (Cambridge : Cambridge University Press, 2022)
The new wave of populism that has emerged over the last five years in Europe and in the US urgently needs to be better understood in a comparative and historical context. Using Italy - including the experiment of a self-styled populist coalition government - as a case study, this book investigates how populists in power borrow, use and manipulate categories of constitutional theory and instruments of constitutional law. Giuseppe Martinico goes beyond treating constitutionalism and populism as purely antithetical to dive deeply into the impact of populism on the activity of some instruments of constitutional democracy, endeavoring to explore their role as possible fora of populist claims and targets of populist attacks. Most importantly, he points to ways in which constitutional democracies can channel populist claims without jeopardizing the legacy of post-World War II constitutionalism. This book is aimed at academics and practicing lawyers interested in populism and comparative constitutional law.
Title from publisher's bibliographic system (viewed on 24 Nov 2021).
Keywords: Populism -- Italy -- Case studies; Populism -- Italy -- History -- 21st century; Populism -- United States -- History -- 21st century; Populism -- Europe -- History -- 21st century